Electrochemical Behaviours of La-Fe Alloys Electrodeposited in DMSO Solution - Lin, Guo; Wei, Yin (Asian Journal of Chemistry, 2010)
The brown metallic luster La-Fe alloy powders were prepared by potentiostatic electrolysis technique with a cathode of fine copper threads in DMSO solution at room temperature. The La-Fe alloy powders containing 28.40-43.54 % lanthanum with the changes of concentration of LaCl3. DMSO solutions show that the different weight of rare earth alloy powders can be obtained by controlling the concentration of lanthanum solution. The size of metal grains is about 0.1 μm to 20 μm. The turning potentials of -2.41, -1.71 and -1.17 V are attributed to reduction of La3+, Fe2+ and Fe3+ ion, respectively. The turning potentials of -3.40 and -1.46 V are assigned to the oxidation of La and Fe metals, respectively.